Efektivitas Balai Latihan Kerja Industri (BLKI) Dalam Peningkatan Keterampilan Tenaga Kerja Pada Program Pembuatan Roti Dan Kue di Kota Balikpapan - Putri, Ghita Chaecarani; Nurmanina, Agustin (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This study aims to examine the learning process, services, and impact of BLKI Balikpapan as a vocational training institution under UPTD which had experienced constraints in operations, facilities, and human resources in the bread and cake making program, currently showing better improvement and attracting public interest. The method used is descriptive qualitative, with primary data collection namely observation and interview techniques involving 3 key informants and 7 main informants, as well as secondary data namely literature study techniques and documentation techniques. By using Kirkpatrick’s four-level Evaluation Theory, including reaction, learning, behavior, and result. The result of the research shows that BLKI Balikpapan bread and cake making program regarding the level of effectiveness is assessed by the main informant 90% delivered related to the learning and reaction stages, 80% related to the behavior and result stages, this is because there are still obstacles, in those two stages. BNSP influences the workforce to increase the value in themselves, BLKI Balikpapan is also an example for the other regional BLKs that are still less active.